Soluble interleukin-2 receptor in monitoring of the treatment course of malignancies – advantages and limitations - Balcerska, Anna; Bień, Ewa (Contemporary Oncology/Współczesna Onkologia, 2003)
The paper summarises the up-to-date knowledge on the role of soluble interleukin-2 receptor (sIL-2Rα) in the monitoring of the clinical course and response to therapy among cancer patients. sIL-2Rα constitutes a subunit a of the membrane receptor for interleukin-2. It is present in body fluids after its release from the cell surface. The increased levels of sIL-2Rα have been stated in a majority of lymphoproliferative haematological disorders as well as in some malignant solid tumours, mainly in a disseminated phase. The precise source and biological significance of high serum levels of sIL-2Rα is not clear, however it has been proved that measurement of sIL-2Rα plays an important role in diagnostics and prognosis in different types of neoplasms. The studies concerning the problem of the clinical significance of sIL-2Rα in the monitoring of disease course in patients suffering from cancer are not numerous and their results are not always evident. The paper also presents a detailed analysis of main factors influencing the serum level of sIL-2Rα. These factors include the age of individuals and some components of antitumour therapy, such as general anaesthesia, surgical procedures, infection and administration of haematopoietic growth factors. The knowledge about these factors is necessary for proper planning of the dates of sIL-2Rα measurement, as well as for adequate interpretation of the results obtained.